Speculation and commodity prices. - Chua, Zhen Chuan. (2011)
This study aims to access the impact of speculation in the futures market on commodities prices. Specifically it aims to find the root cause of the recent commodity price hike so as to access if current policy is sufficient in tackling trending prices. The results show that prices in the long term are mainly caused by demand and supply factors such as production, for crude oil and wheat. In the case of crude oil, growing import levels of rapidly developing giants such as China and India does constitute a significant portion of the rise in crude prices. This could be the focus of future works as the energy intensity of China and India is almost certain to grow rapidly. Attempts at investigating the impact of declining spare capacity yields no results. This could be attributed to the ever rising oil exploration works, which increases world proved reserves, as steeply rising prices make these explorations more profitable. The upward impact on price by falling expected future output is moderated by new oil finds. Speculation is not found to be a cause of rising price for wheat and sugar, but found to be a minor contributor for crude oil. However the impact of non-commercial speculation is very small relative to macroeconomic and fundamental influences.